Perforated appendix! An experience of a Public teaching hospital - Naqqash Adnan , Ahmed Mujtaba Malik , Gohar Rasheed, Maryam Iftikhar, Maariah Asif, Jahangir Sarwar Khan , Naqqash Adnan , Ahmed Mujtaba Malik , Gohar Rasheed, Maryam Iftikhar, Maariah Asif, Jahangir Sarwar Khan (Journal of Rawalpindi Medical College, 2019)
Introduction The most common cause of non-traumatic acute abdominal pain as well as the most common acute abdominal condition presenting to Surgical Emergency is none other than Acute Appendicitis hence it becomes the most common entity undergoing surgery in Emergencies all over the world. The lifetime risk for someone to develop acute appendicitis is 8.6% and 6.7% for males and females respectively, with 90% found in children and young adults and 10% in patients over 60 years of age.1 Increasing age or in other words decreasing immunity does affect the incidence of perforated appendix as we see the the perforation rate in acute appendicitis is approximately 20~30% but as the age goes beyond 60 years it inclines to 32-72%.2 Delay in the diagnosis caused by indefinite history and physical examination tends to contribute to higher incidence of perforated appendix as reported by Siripong et al. In another study the risk factors that were found to be associated with perforated appendicitis were male sex, fever ≥ 38°C, anorexia, and duration of pain in the pre-admission period.3 In one of the the study pre-hospital delays were exceeding related to perforation as compared to in-hospital delays which was explainable because of a linear relationship present among the pathological grade to hospital interval ratio , thus leading to increased risk of perforation.4 As far as the blood work was concerned , an increase in Total Leucocyte count with majority being polymorphonuclear leukocytes (PMN), and raised C-reactive protein (CRP) levels were found to be responsible for substantial increment in the risk and gravity of complications in appendicitis. Presence of comorbid diseases didn't show any significant affect on perforation rate.5